2021
DOI: 10.20517/2347-9264.2021.03
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting pedicled latissimus dorsi flaps in head and neck reconstruction: contrasting shoulder morbities across mysofascial flaps

Abstract: Revisiting pedicled latissimus dorsi flaps in head and neck reconstruction: contrasting shoulder morbities across mysofascial flaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Free flaps based on the subscapular arterial system provide the most versatile of the osseous flaps given the option for separate segments of bone, multiple skin paddles, and significant volume to fill the defect. The scapular tip-free flap from the angular artery provides a long pedicle length and has morphologic similarity to the palate [8] . Case series at multiple institutions have indicated that osteotomies and dental implants can be used successfully in scapular tip-free flaps for mandibular reconstruction, although there is limited data on these techniques in maxillary reconstruction [6,20,21] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Free flaps based on the subscapular arterial system provide the most versatile of the osseous flaps given the option for separate segments of bone, multiple skin paddles, and significant volume to fill the defect. The scapular tip-free flap from the angular artery provides a long pedicle length and has morphologic similarity to the palate [8] . Case series at multiple institutions have indicated that osteotomies and dental implants can be used successfully in scapular tip-free flaps for mandibular reconstruction, although there is limited data on these techniques in maxillary reconstruction [6,20,21] .…”
Section: Discussionmentioning
confidence: 99%
“…The radial forearm, fibula, iliac crest, and scapula osteocutaneous free flap have been described for use in boney reconstruction of maxillary defects [2,4] . Previous studies have demonstrated the utility of the scapula tip for midfacial reconstruction [5][6][7][8] . The scapula tip-free flap has advantages over the fibula or iliac crest related to the chimeric nature of the subscapular vascular system allowing for multiple tissue types, long vascular pedicle, ability to perform extirpation and flap harvest concurrently, acceptable donor site morbidity, and excellent versatility in rebuilding 3-dimentional bone structures of the craniofacial skeleton [5,6,8,9] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 However, current positioning systems allow for two team approaches to the harvest of both LSBFF and STFF. 9,10 The following pictorial essay describes the positioning pearls, operative technique, and clinical considerations for each of these free flaps. Institutional approval for this study was provided through the University of Michigan with informed consent obtained from all depicted patients.…”
Section: Introductionmentioning
confidence: 99%